Thermostability enhancement of xylanase aspergillus fumigatus rt-1 - Abdul Wahab, Mohd Khairul Hakimi (ELSEVIER, 2016)
This study aimed to improve the thermostability of endo -1,4-xylanase (afxynG1) from Aspergillus fumi- gatus RT-1 using error-prone PCR. Since the wild type enzyme has an optimum temperature stability at 50 ◦ C, the improvement of its stability will widen its application in industries with operating processes at higher temperatures. A library containing approximately 5000 afxynG1 mutants was generated and ther- mally screened at 60 ◦ C for 30 min. Four mutants (T16A/T39I/L176Q, S68R, A60D and Q47P/S159R) were selected for enzymatic characterization because of their higher catalytic activity compared to the wild type. Among these mutants, the mutant T16A/T39I/L176Q showed highest stability at 70 ◦ C and retained 45.9% of its activity after 60 min of incubation while the wild type had lost its activity completely after 50 min of incubation. The other mutants, A60D, S68R and Q47P/S159R also showed improvement in ther- mostability by retaining 33.2%, 25.8% and 23.8% of their activity respectively. The optimum temperature for mutants also significantly increased. The optimum temperature for T16A/T39I/L176Q increased up to 70 ◦ C, followed by A60D increased up to 60 ◦ C while the rest remained the same, similar to the wild type enzyme. The mutant T16A/T39I/L176Q had the highest half-life time (t 1/2 ) of 42 min at 70 ◦ C, which is a 3.5-fold increase compared to the wild type enzyme which only showed a t 1/2 of 12 min at 70 ◦ C. This is followed by mutant A60D, t 1/2 of 31 min (2.7-fold), S68R, t 1/2 of 29 min (2.4-fold) and Q47P/S159R, t 1/2 of 27 min (2.25-fold). Based on homology modelling conducted to analyze the mutants’ structures , it showed that hydrophobicity and hydrogen bonds were the driving forces that lead to the improvement of the thermal stability of these xylanase mutants.